Coping With Extreme Events: Growth and Water‐Use Efficiency of Trees in Western Mexico During the Driest and Wettest Periods of the Past One Hundred Sixty Years. Issue 11 (15th November 2019) - Castruita‐Esparza, Luis U.; Silva, Lucas C.R.; Gómez‐Guerrero, Armando; Villanueva‐Díaz, José; Correa‐Díaz, Arian; Horwath, William R.
Abstract: Understanding how trees respond to extreme events is important to predict how climate change will impact forests in the future. In this study, we report changes in radial growth and tree‐ring carbon (δ 13 C) and oxygen (δ 18 O) stable isotope ratios of Pseudotsuga menziesii (Douglas‐fir) in western Mexico. Tree growth was compared with δ 13 C and δ 18 O ratios recorded during dry and wet periods caused by El Niño‐Southern Oscillation since 1850. The three driest and three wettest events during the studied period caused tree growth decline of up to 50% followed by 6–10 years of slow recovery until baseline growth was regained. Wet events resulted in up to 17% growth increase, a positive effect that persisted for no more than 3–5 years. Stable isotope ratios recorded physiological adjustments that in some cases correlated significantly with tree growth. Excursions in tree‐ring Δ 13 C and δ 18 O isotope ratios suggest that trees cope with dry and wet periods with proportional but divergent adjustments in photosynthesis versus stomatal conductance. Notably, the intrinsic water‐use efficiency—that is, the ratio between carbon assimilation and water loss through transpiration—was positively correlated with tree basal growth only during dry periods. We found no significant correlations between growth and intrinsic water‐use efficiency during wet periods. Contrary to expectations, rising CO2 levels over the past 160 years did not affect tree growth response to precipitation variability. Key Points: To quantify the response of Douglas‐fir trees to dry and wet events, we measured tree rings and C and O stable isotopes since 1850 Tree growth decreased up to 50% following extreme drought events, an impact that lasted up to 10 years Each extreme wet event resulted in up to 17% of growth increase, an effect that lasted up to 5 years